Statutory health insurance in Germany: a health system shaped by 135 years of solidarity, self-governance, and competition - Busse, Reinhard; Bärnighausen, Till (The lancet, 2017)
Summary Bismarck's Health Insurance Act of 1883 established the first social health insurance system in the world. The German statutory health insurance system was built on the defining principles of solidarity and self-governance, and these principles have remained at the core of its continuous development for 135 years. A gradual expansion of population and benefits coverage has led to what is, in 2017, universal health coverage with a generous benefits package. Self-governance was initially applied mainly to the payers (the sickness funds) but was extended in 1913 to cover relations between sickness funds and doctors, which in turn led to the right for insured individuals to freely choose their health-care providers. In 1993, the freedom to choose one's sickness fund was formally introduced, and reforms that encourage competition and a strengthened market orientation have gradually gained importance in the past 25 years; these reforms were designed and implemented to protect the principles of solidarity and self-governance. In 2004, self-governance was strengthened through the establishment of the Federal Joint Committee, a major payer-provider structure given the task of defining uniform rules for access to and distribution of health care, benefits coverage, coordination of care across sectors, quality, and efficiency. Under the oversight of the Federal Joint Committee, payer and provider associations have ensured good access to high-quality health care without substantial shortages or waiting times. Self-governance has, however, led to an oversupply of pharmaceutical products, an excess in the number of inpatient cases and hospital stays, and problems with delivering continuity of care across sectoral boundaries. The German health insurance system is not as cost-effective as in some of Germany's neighbouring countries, which, given present expenditure levels, indicates a need to improve efficiency and value for patients.